Primary carnitine deficiency: Estimation of prevalence in Chinese population and insights into newborn screening - Ji, Xiaoshan; Ge, Yanzhuang; Ni, Qi; Xu, Suhua; Xiong, Zhongmeng; Yang, Lin; Hu, Liyuan; Cao, Yun; Lu, Yulan; Wei, Qiufen; Kang, Wenqing; Zhuang, Deyi; et al. (Frontiers in Genetics, 2023)
Primary carnitine deficiency (PCD) caused by pathogenic variants in the solute carrier family 22 member 5 (SLC22A5) gene is a rare autosomal recessive disease that results in defective fatty acid oxidation. PCD can be detected through tandem mass spectrometry (MS/MS), but transplacental transport of free carnitine from the mothers may cause false negatives or positives during newborn screening. This study aimed to analyze the genetic characteristics of SLC22A5 and estimate the prevalence of PCD in Chinese population, providing useful information for newborn screening and genetic counseling. We manually curated SLC22A5 pathogenic or likely-pathogenic (P/LP) variants according to American College of Medical Genetics and Genomics (ACMG) guidelines and identified 128 P/LP variants. Based on the China Neonatal Genomes Project (CNGP), the estimated PCD prevalence was 1:17,456, which was higher than 2 other populations. The genotype-phenotype association analysis showed that patients carrying homozygous c.760C>T and c.844C>T were more likely to present cardiomyopathy, while carrying homozygous c.1400C>G were more likely to be asymptomatic (all P value < 0.05). We found there was no significant difference in initial C0 concentrations between patients and carriers, while there was a significant difference in the second-tier screening of C0 concentration between them (P value < 0.05). We established a cost-effective variants panel containing ten high-frequency sites and developed a screening algorithm incorporating gene panels with MS/MS, which could rescue one more patient who was undetected from MS/MS. In conclusion, the prevalence of PCD in the Chinese population is relatively high. The combination of conventional newborn screening (NBS) with genetic sequencing is suggested for early diagnosis of PCD.